2015
DOI: 10.2106/jbjs.m.01360
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Patients Undergoing Distal Tibial Osteotomy without Fibular Osteotomy for Medial Ankle Arthritis with Mortise Widening

Tae-Keun Ahn,
Young Yi,
Jae-Ho Cho
et al.

Abstract: Distal tibial osteotomy without fibular osteotomy reduces pain in the short term in patients with ankle arthritis, a widened mortise, and minimal talar tilt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
121
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(126 citation statements)
references
References 14 publications
(10 reference statements)
4
121
1
Order By: Relevance
“…Medial opening-wedge supramalleolar osteotomy with fibular osteotomy can cause more lateral translation of the talus than medial opening-wedge supramalleolar osteotomy without fibular osteotomy. Combined fibular osteotomy and distal tibial osteotomy facilitates translation of the distal fragment, but the amount of shift of the osteotomized fragment is limited by the fibula after distal tibial osteotomy without fibular osteotomy (17,18). Our results coincide with these findings, showing that combined fibular osteotomy significantly decreases the talar translation ratio.…”
Section: Discussionsupporting
confidence: 86%
“…Medial opening-wedge supramalleolar osteotomy with fibular osteotomy can cause more lateral translation of the talus than medial opening-wedge supramalleolar osteotomy without fibular osteotomy. Combined fibular osteotomy and distal tibial osteotomy facilitates translation of the distal fragment, but the amount of shift of the osteotomized fragment is limited by the fibula after distal tibial osteotomy without fibular osteotomy (17,18). Our results coincide with these findings, showing that combined fibular osteotomy significantly decreases the talar translation ratio.…”
Section: Discussionsupporting
confidence: 86%
“…In previous studies, the authors recommended fibular osteotomy as a standard procedure for the treatment of varus ankle OA [2, 12, 16]. However, some studies recommended preserving the fibula in all cases [3, 11, 17, 18]. We based the decision to perform the fibular osteotomy on the pre- and intraoperative evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TT in SMOT is highly controversial. Some authors have reported a significant decrease of the TT [4, 7, 8, 11, 17]; however, others have not [3, 12, 15, 19]. Tanaka et al [12] reported that in all patients with a preoperative TT greater than 10°, the joint space did not return to normal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations